Peningkatan Kompetensi Siswa Melalui Kegiatan Literasi dan Numerasi: Pengabdian - Astri Yulia Rohmah; Romadhoni, Erina Fitria; Eniah, Nur; Fauzi, Maulidza Nur; Wahyono, Didik Puji (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the impact of literacy and numeracy activities through the Literacy and Numeracy Festival on improving the competencies of students at SMP Negeri 1 Sarirejo. The research employed a qualitative descriptive approach and was conducted directly through the Teaching Campus program. The method included a pre-test to assess students’ initial abilities, literacy and numeracy treatments conducted for 30 minutes after school hours, implementation of the Literacy and Numeracy Festival and a post-test to evaluate outcomes. Data collection techniques involved observation, documentation and analysis of learning evaluation results. The findings showed a significant improvement in students’ literacy and numeracy competencies. The average literacy score increased from 59 to 92 points, while the numeracy score rose from 58.6 to 91.8 points. Activities such as word games, functional text analysis, and contextual mathematical problem-solving fostered active student engagement, enhanced comprehension, perseverance, and confidence. The Literacy and Numeracy Festival proved effective as a creative and participatory contextual learning strategy and is therefore recommended for replication in other schools to strengtheliteracy and numeracy culture and improve the quality of education.